„Nostalgia” i inne opowiadania Nadieżdy Teffi, czyli Rosjanie w Paryżu lat 20. XX wieku - Bielniak, Nel (Studia Rossica Posnaniensia, 2019)
In her humorous 1920s short stories Teffi shows the dramatic situation of Russian diaspora in Paris mainly through the prism of ordinary emigrants. The writer pays attention, among others, to such issues connected with the life of refugees as isolation, alienation, poverty, prurient nostalgia or national identity.